Biosynthesis of the Fluorinated Natural Product Nucleocidin in Streptomyces calvus Is Dependent on the bldA‐Specified Leu‐tRNAUUA Molecule. Issue 17 (22nd October 2015) - Zhu, Xi Ming; Hackl, Stefanie; Thaker, Maulik N.; Kalan, Lindsay; Weber, Claudia; Urgast, Dagmar S.; Krupp, Eva M.; Brewer, Alyssa; Vanner, Stephanie; Szawiola, Anjuli; Yim, Grace; Feldmann, Jörg; et al.
Abstract: Nucleocidin is one of the very few natural products known to contain fluorine. Mysteriously, the nucleocidin producer Streptomyces calvus ATCC 13382 has not been observed to synthesize the compound since its discovery in 1956. Here, we report that complementation of S. calvus ATCC 13382 with a functional bldA ‐encoded Leu‐tRNA UUA molecule restores the production of nucleocidin. Nucleocidin was detected in culture extracts by 19 F NMR spectroscopy, HPLC‐ESI‐MS, and HPLC‐continuum source molecular absorption spectroscopy for fluorine‐specific detection. The molecule was purified from a large‐scale culture and definitively characterized by NMR spectroscopy and high‐resolution MS. The nucleocidin biosynthetic gene cluster was identified by the presence of genes encoding the 5′‐ O ‐sulfamate moiety and confirmed by gene disruption. Two of the genes within the nucleocidin biosynthetic gene cluster contain TTA codons, thus explaining the dependence on bldA and resolving a 60‐year‐old mystery. Abstract : Missing since 1956 : The biosynthesis of nucleocidin in Streptomyces calvus has been restored by complementation with a functional bldA ‐encoded Leu‐tRNA UUA molecule. Nucleocidin was detected in culture extracts, purified, and characterized. Its biosynthetic gene cluster was identified and confirmed by gene disruption.